2012
DOI: 10.1088/0004-637x/758/2/128
|View full text |Cite
|
Sign up to set email alerts
|

On Dark Peaks and Missing Mass: A Weak-Lensing Mass Reconstruction of the Merging Cluster System A520,

Abstract: Merging clusters of galaxies are unique in their power to directly probe and place limits on the self-interaction cross-section of dark matter. Detailed observations of several merging clusters have shown the intracluster gas to be displaced from the centroids of dark matter and galaxy density by ram pressure, while the latter components are spatially coincident, consistent with collisionless dark matter. This has been used to place upper limits on the dark matter particle self-inteaction crosssection of order… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
85
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(91 citation statements)
references
References 63 publications
5
85
1
Order By: Relevance
“…The NE clump is aligned with the elongated mass distribution (NE to SW): structures 2+3 in Fig. 2 by Clowe et al (2012). The diffuse emission at the shock location in the SW is observed to correspond with the 4-7 structures in the same figure.…”
Section: Radio-halo Naturementioning
confidence: 65%
See 2 more Smart Citations
“…The NE clump is aligned with the elongated mass distribution (NE to SW): structures 2+3 in Fig. 2 by Clowe et al (2012). The diffuse emission at the shock location in the SW is observed to correspond with the 4-7 structures in the same figure.…”
Section: Radio-halo Naturementioning
confidence: 65%
“…In between, a depression in the radio surface brightness can be observed. The mass distribution (Clowe et al 2012) and the diffuse radio emission are clearly linked. Indeed, we note that the nonthermal emission permeates regions of high mass.…”
Section: Radio-halo Naturementioning
confidence: 94%
See 1 more Smart Citation
“…This paradigm provides a natural explanation to the apparent conspiracy between the observed baryonic distribution and the gravitational force in various types of galaxies (see, e. g. Famaey & McGaugh 2012;McGaugh et al 2016;Lelli et al 2016). Nevertheless, the successes of the paradigm are mostly limited to galactic scales (for problems at other scales, see, e.g., Skordis et al 2006;Clowe et al 2006;Angus 2008;Ibata et al 2011;Dodelson 2011;Clowe et al 2012;Harvey et al 2015). This could mean that it is either an effective way to predict how dark matter (DM) is arranged in galaxies, or that it is an effective modification of gravity resulting from a broader theory of the dark sector (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Markevitch et al 2002) and of the gravitational lensing (Clowe et al 2006, Bradac et al 2006 showed that distributions of the hot gas in the Intra Cluster Medium (ICM) and of the DM are centered at different positions. The other case of A520 where there is some spatial offset between DM and baryons is not a very clean case to study (Mahdavi et al 2007, Clowe et al 2012.…”
Section: Introductionmentioning
confidence: 99%